Circulating estrogens and postmenopausal ovarian cancer risk in the Women’s Health Initiative Observational Study - Trabert, Britton (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Hormonal and reproductive factors contribute to the development of ovarian cancer, but few studies have examined associations between circulating estrogens and estrogen metabolites and ovarian cancer risk. We evaluated whether serum estrogens and estrogen metabolite levels are associated with ovarian cancer risk among postmenopausal women in a nested case-control study in the Women’s Health Initiative (WHI) Observational Study (OS). METHODS: We selected all 169 eligible epithelial ovarian cancer cases and 412 matched controls from women enrolled in WHI-OS who were not using menopausal hormones at baseline. Baseline levels of 15 estrogens and estrogen metabolites were measured via LC-MS/MS. Associations with ovarian cancer risk overall and stratified by histologic subtype (serous/non-serous) were analyzed using logistic regression. The mean time from serum collection to cancer diagnosis was 6.9 years. RESULTS: Overall we observed modest ovarian cancer risk associations among women with higher levels of estrone [Odds Ratio (95% Confidence Interval) quintile (Q)5 vs. Q1: 1.54 (0.82–2.90), p-trend=0.05], as well as 2- and 4-methoxyestrone metabolites [2.03 (1.06–3.88), p-trend=0.02; 1.86 (0.98–3.56), p-trend=0.01, respectively]. Associations of estrogens and estrogen metabolites varied substantially by histologic subtype. Associations with serous tumors were universally null, while estrone (2.65 (1.09–6.45), p-trend=0.01, p-heterogeneity=0.04), unconjugated estradiol (2.72 (1.04–7.14), p-trend=0.03, p-heterogeneity=0.02) and many of the 2-, 4-, and 16-pathway metabolites were positively associated with non-serous tumors. CONCLUSIONS: Our study provides novel molecular data showing an association of the parent estrogens and several estrogen metabolites with non-serous ovarian cancers. IMPACT: These findings further support the heterogeneous etiology of ovarian cancer.